A study on Candida biofilm growth characteristics and its susceptibility to aureobasidin A (Estudio de las características de biopelículas de Candida y su sensibilidad a la aureobasidina A) - Munusamy, Komathy; Vadivelu, Jamuna; Tay, Sun Tee (Elsevier, 2018)
Background: Biofilm is known to contribute to the antifungal resistance of Candida yeasts. Aureobasidin A (AbA), a cyclic depsipeptide targeting fungal sphingolipid biosynthesis, has been shown to be effective against several Candida species. Aims: The aim of this study was to investigate Candida biofilm growth morphology, its biomass, metabolic activity, and to determine the effects of AbA on the biofilm growth. Methods: The biofilm forming ability of several clinical isolates of different Candida species from our culture collection was determined using established methods (crystal violet and XTT assays). The determination of AbA planktonic and biofilm MICs was performed based on a micro-broth dilution method. The anti-biofilm effect of AbA on Candida albicans was examined using field emission scanning electron microscope (FESEM) analysis. Results: A total of 35 (29.7%) of 118 Candida isolates were regarded as biofilm producers in this study. Candida parapsilosis was the largest producer, followed by Candida tropicalis and C. albicans. Two morphological variants of biofilms were identified in our isolates, with 48.6% of the isolates showing mainly yeast and pseudohyphae-like structures, while the remaining ones were predominantly filamentous forms. The biofilm producers were divided into two populations (low and high), based on the ability in producing biomass and their metabolic activity. Candida isolates with filamentous growth, higher biomass and metabolic activity showed lower AbA MIC 50 (at least fourfold), compared to those exhibiting yeast morphology, and lower biomass and metabolic activity. The observation of filament detachment and the almost complete removal of biofilm from AbA-treated C. albicans biofilm in FESEM analysis suggests an anti-biofilm effect of AbA. Conclusions: The variability in the growth characteristics of Candida biofilm cultures affects susceptibility to AbA, with higher susceptibility noted in biofilm cultures exhibiting filamentous form and high biomass/metabolic activity.